PENTINGNYA PENGAWASAN DI KAWASAN KESELAMATAN OPERASI PENERBANGAN BANDAR UDARA HALIM PERDANA KUSUMA - JAKARTA - Putra, Satria Kurniawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Aviation safety in the airport area, so far, has become a mandatory or mandatory obligation for all airlines and airport managers. The regulations also explain the Safety Management System (SMS) as an effort to prevent flight accidents or other extraordinary events. Regulations regarding aviation safety have been regulated by the Government of Indonesia, in Law Number 1 of 2009 concerning Aviation. Furthermore, there is also a Regulation of the Minister of Transportation of the Republic of Indonesia Number 93 of 2019 concerning the National Aviation Safety Program. All regulations that are enforced are none other than in the context of improving national aviation safety. The problem that often occurs at the airport is wild animals entering the runway area to the plane parking lot or kites breaking up that enter the airport. This must be taken seriously, there are hot air balloons and laser beams and what is being developed in society is drones. Prohibited from being at the airport, constructing buildings or carrying out other activities in or around the airport that could endanger the security and safety of flights